Descendants of Boruta – Boruccy from Borucice in the Łęczyca Region - Nowak, Tadeusz (Diabeł Boruta w dawnej kulturze polskiej, 2021)
Borucice (poviat of Łęczyca) emerged as a result of ownership divisions of the village of Sobiesławice. During the Jagiellonian era, descendants of Boruta from Sobiesławice, it means Boruccy from Borucice, who were a petty-noble family. In 1555 Maciej Borucki killed the townsman of Łęczyca, Walenty. Perhaps this event contributed to the creation of the legend of Boruta devil, who, pretending to be a nobleman, posed a major threat to the inhabitants of Łęczyca and nearby towns.